Light Paraffinic Naphtha to BTX Aromatics over Metal‐Modified Pt/ZSM‐5. Issue 44 (23rd November 2020) - Ellouh, Mohammed; Qureshi, Ziyauddin S.; Aitani, Abdullah; Akhtar, Muhammad Naseem; Jin, Yaming; Koseoglu, Omer; Alasiri, Hassan
Abstract: We investigated the conversion of light paraffinic naphtha (C5‐C6) into BTX (benzene, toluene, and xylenes) aromatics using 1.0 wt % Pt‐M/ZSM‐5 (modifier M=1 wt% Zn, 2 wt % of Fe, La, Ga) prepared using wet‐impregnation method. The effects of Pt and modifier on light naphtha conversion, yield and aromatic selectivity (benzene, toluene, xylene, C9+ aromatics) were studied in fixed‐bed flow reactor in atmospheric pressure, at 550 °C, and WHSV 1.0 h −1 . Catalytic efficiency of modified Pt or Pt‐M ZSM‐5 catalysts has been equated to conventional ZSM‐5 [Si/Al2 =30] catalyst. While the yield of total aromatics was slightly increased over Pt/ZSM‐5 comparison to parent ZSM‐5 from 32 wt % to 37 wt %, the value for in situ formed mesoporous Pt‐Ga/ZSM‐5 was significantly improved reaching 60 wt %. The higher selectivity to aromatics is attributed to the induced mesoporous volumes and dehydrogenation activity of Ga species. These species associated with Pt were effective in the conversion of light naphtha to olefins, which later converted into aromatics by secondary reactions: cracking, isomerization and dimerization. The Pt‐Ga/ZSM‐5 showed good stability toward the selective production of aromatics at a low toluene/benzene ratio ∼0.5 due to Pt component. Abstract : A catalytic process developed to transform light paraffinic naphtha stream (C5‐C6) into BTX aromatics using Pt‐M/ZSM‐5 (modifier M=Zn, Fe, La, Ga) modified zeolite catalysts prepared using a wet‐impregnation method. Pt‐Ga/ZSM‐5 catalyst significantly improved aromatics yield (60 wt %) due to the induced mesoporous volumes and dehydrogenation activity of Ga species. Pt‐Ga/ZSM‐5 modified zeolite catalyst shows the lowest coke yield and good short‐term (24 h) stability toward aromatics with low toluene/benzene ratio ∼0.5.